2015
DOI: 10.1016/j.bbamcr.2014.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Efficient export of human growth hormone, interferon α2b and antibody fragments to the periplasm by the Escherichia coli Tat pathway in the absence of prior disulfide bond formation

Abstract: Numerous therapeutic proteins are expressed in Escherichia coli and targeted to the periplasm in order to facilitate purification and enable disulfide bond formation. Export is normally achieved by the Sec pathway, which transports proteins through the plasma membrane in a reduced, unfolded state. The Tat pathway is a promising alternative means of export, because it preferentially exports correctly folded proteins; however, the reducing cytoplasm of standard strains has been predicted to preclude export by Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 29 publications
7
70
0
Order By: Relevance
“…We further confirmed that the disulphide bonds remain reduced during the purification process; Supplementary data A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 12 We have previously shown that a different scFv could be exported in wild type or CyDisCo cells (i.e. in either the reduced or oxidised form; [23]); we therefore first tested whether the disulphide bonding status affects export of scFvM by Tat in these strains. The protein was expressed with a TorA signal peptide, and reveals that export is ca.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…We further confirmed that the disulphide bonds remain reduced during the purification process; Supplementary data A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 12 We have previously shown that a different scFv could be exported in wild type or CyDisCo cells (i.e. in either the reduced or oxidised form; [23]); we therefore first tested whether the disulphide bonding status affects export of scFvM by Tat in these strains. The protein was expressed with a TorA signal peptide, and reveals that export is ca.…”
Section: Resultssupporting
confidence: 74%
“…To this end we chose an scFv (termed scFvM, to distinguish it from the different scFv used by Alanen et al [23]) and we then generated and tested a range of mutants, including some sourced from a biophysical study of the scFv and mutants in solution (manuscript in preparation). The predicted structure scFvM, based on homology modelling with PDB file 2GHW, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PglB, as highlighted previously, is a membrane bound protein located in the periplasm, so is already present. As for the target protein, there are multiple pathways available that will direct the target protein to this part of the cell, including the TAT export system [40], SRP pathway [41], and sec transport system [42]. The most utilized methodology is the sec transport system, which requires the addition of a 22 amino acid leader sequence at the N-terminus of the polypeptide chain.…”
Section: Periplasmic Localizationmentioning
confidence: 99%